Fedor Krause (1857-1937) and His Innovations in Neurosurgery. (October 2019) - Laios, Konstantinos; Lytsikas-Sarlis, Pavlos; Kostoulas, Georgios; Zamparas, Athanasios; Mavrommatis, Evangellos; Konofaou, Vassiliki; Androutsos, George
Although Ernst von Bergmann (1837-1907) is considered the father of neurosurgery in Germany, Fedor Krause (1857-1937) should be considered as its main founder. He was principally a general surgeon but he had a special interest in neurosurgery, a field in which he introduced many new techniques. He also fabricated innovative surgical methods for the treatment of patients with epilepsy.